2021
DOI: 10.1016/j.jare.2021.06.001
|View full text |Cite
|
Sign up to set email alerts
|

Hyperoside attenuates non-alcoholic fatty liver disease in rats via cholesterol metabolism and bile acid metabolism

Abstract: Graphical abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
35
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 65 publications
(41 citation statements)
references
References 61 publications
1
35
0
Order By: Relevance
“…Although previous studies on the antisteatotic effects of Hyp are scarce, this compound has been reported to reduce hepatic fat accumulation in rodents fed a high-fat diet and alcohol and in diabetes-induced rats [ 39 , 60 , 61 , 74 , 75 , 76 ]. The antisteatotic activity of Hyp in high-fat diet-induced C57BL/6 mice and diabetes-induced rats occurred with liver weight loss and reduced hepatic lipid contents, such as TG, TC, and NEFA [ 60 , 74 ].…”
Section: Pharmacological Effects Of Hyperoside In Liver Diseasesmentioning
confidence: 99%
See 4 more Smart Citations
“…Although previous studies on the antisteatotic effects of Hyp are scarce, this compound has been reported to reduce hepatic fat accumulation in rodents fed a high-fat diet and alcohol and in diabetes-induced rats [ 39 , 60 , 61 , 74 , 75 , 76 ]. The antisteatotic activity of Hyp in high-fat diet-induced C57BL/6 mice and diabetes-induced rats occurred with liver weight loss and reduced hepatic lipid contents, such as TG, TC, and NEFA [ 60 , 74 ].…”
Section: Pharmacological Effects Of Hyperoside In Liver Diseasesmentioning
confidence: 99%
“…Regarding the underlying mechanisms attributed to the antisteatotic effects of Hyp, it exerted beneficial actions in (1) maintaining hepatic lipid and glucose homeostasis by activating peroxisome proliferator-activated receptor gamma (PPARγ), which lowers glucose levels and reverses lipotoxicity; (2) reducing oxidative stress; (3) synthesizing bile acids from cholesterol by activating key catalytic enzymes CYP7A1 and CYP27A1; (4) increasing the β-oxidation of free fatty acids by the activation of nuclear farnesoid X receptor (FXR) and transcription factor liver X receptor (LXR)α implicated in lipid oxidation; and (5) inhibiting de novo lipogenesis by modulating hepatic de novo lipogenesis markers acetyl-CoA carboxylase (ACC) and sterol regulatory element binding proteins (SREBP)1,2 in vivo and in vitro [ 39 , 61 , 74 , 75 , 76 ] ( Table 3 ).…”
Section: Pharmacological Effects Of Hyperoside In Liver Diseasesmentioning
confidence: 99%
See 3 more Smart Citations